Perkembangan Lembaga Pendidikan Islam di Pidie - Darwin (Madrasah Aliyah Negeri 1 Pidie, 2022)
This article aims to describe the development of Islamic Education Institutions in the Pidie Regency. The method used in this article is a literature study, and data sourced from books, journals, and other literature relevant to this study. The results of the study show that the development of Pidie Islamic educational institutions goes hand in hand with changes in educational institutions in Indonesia in general because Pidie is an integral part of the unitary state of the Republic of Indonesia. Islamic educational institutions in Pidie are gradually turning into modern educational institutions, but still, maintain their identity as an Islamic educational institution inherited from Aceh's history. Thus, even though madrasas exist and dominate as Islamic educational institutions, every child born in Aceh still receives an education in Meunasah and Dayah throughout all Gampong in Aceh. Abstrak Artikel ini bertujuan untuk mendeskripsikan tentang perkembangan Lembaga Pendidikan Islam di Kabupaten Pidie. Metode yang digunakan dalam artikel ini merupakan studi literatur yang bersumber dari buku-buku, jurnal-jurnal dan kepustakaan lainnya yang relevan dengan kajian ini. Hasil kajian menunjukkan bahwa perkembangan lembaga pendidikan Islam Pidie berjalan beriringan dengan perubahan-perubahan pada lembaga pendidikan di Indonesia secara umum karena Pidie merupakan bagian integral dari negara kesatuan republik Indonesia. Lembaga pendidikan Islam di Pidie secara bertahap berubah menjadi lembaga pendidikan modern, tetapi tetap mempertahankan identitasnya sebagai lembaga pendidikan Islam warisan sejarah Aceh. Sehingga, meskipun madrasah telah eksis dan mendominasi sebagai lembaga pendidikan Islam, namun setiap anak yang lahir di Aceh masih tetap mengenyam pendidikan di meunasah dan dayah-dayah tradisional yang tersebar di seluruh Gampong yang ada di Aceh.